Kenya adopts a Bioenergy Strategy with support from ICRAF - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
ICRAF contributes to the development of Kenya's Bioenergy Strategy, which will provide a road map for the country to manage and sustainably harness its bioenergy resources during 2020?2027.